A long cycle-life and high safety Na+/Mg2+ hybrid-ion battery built by using a TiS2 derived titanium sulfide cathode. Issue 2 (6th December 2016) - Bian, Xiaofei; Gao, Yu; Fu, Qiang; Indris, Sylvio; Ju, Yanming; Meng, Yuan; Du, Fei; Bramnik, Natalia; Ehrenberg, Helmut; Wei, Yingjin
Abstract : A hybrid-ion battery was designed using Mg as the anode and TiS2 as the cathode, combined with a Na + /Mg 2+ hybrid electrolyte. Abstract : The practical uses of magnesium-ion batteries are hindered by their poor rate capability and fast capacity decay. Moreover, traditional sodium ion batteries suffer from serious safety problems resulting from the sodium dendrites formed on the anode. In order to circumvent these problems, we designed a highly reversible Na + /Mg 2+ hybrid-ion battery composed of a metallic Mg anode, a TiS2 derived titanium sulfide cathode and a 1.0 M NaBH4 + 0.1 M Mg(BH4 )2 /diglyme hybrid electrolyte. The battery showed remarkable electrochemical performances with a large discharge capacity (200 mA h g −1 at the 1C rate), high rate capability (75 mA h g −1 at the 20C rate) and long cycle life (90% capacity retention after 3000 cycles). Moreover, it exhibited excellent safety properties due to dendrite-free Mg deposition of the anode and the high thermal stability of the cathode. These merits demonstrate the great potential of the reported Na + /Mg 2+ hybrid-ion battery for large-scale energy storage.